The Effect of Audit Quality, Previous Year's Audit Opinion, And Company Growth on the Acceptance of Going Concern Audit Opinions: Pengaruh Kualitas Audit, Opini Audit Tahun Sebelumnya, Dan Pertumbuhan Perusahaan Terhadap Penerimaan Opini Audit Going Concern - Dewi Anggraeni; Nurasik (Academia Open, 2021)
This study aims to analyze the Effect of Audit Quality, Previous Year's Audit Opinion, and Company Growth on the Acceptance of Going Concern Audit Opinions in Food and Beverage Companies Listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. The sampling method used is purposive sampling method. The number of companies that were sampled in this study were 10 Food and Beverage companies listed on the IDX in the 2015-2019 period. The data used is secondary data. The data analysis method used in this study is Logistic Regression with SPSS 23. The results of this study indicate that audit quality has an effect on the acceptance of going concern audit opinions. The previous year's audit opinion has an effect on the acceptance of going-concern audit opinion. Company growth has an effect on going concern audit acceptance.